The Use of The Lectora Inspire Assisted Poe Learning Model on Body Defense System Material - Adawiyah, Ai Siti Rabiah; Suhada, Idad; Listiawati, Milla (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2023)
The POE (Predict-Observe-Explain) model is a constructivism-based learning model that allows students to build their own knowledge. The purpose of this study was to assess the effect of the Lectora Inspire-assisted POE learning model on students' critical thinking skills. The research sample was 32 students of class XI MIPA 1 as the control class and 32 students of XI MIPA 3 as the experimental class. This type of research is a quasi-experimental research design with nonequivalent control group design where in this study one group was given learning treatment using the Predict-Observe-Explain (POE) model assisted by Lectora Inspire and the other group was not given any treatment. The data was obtained through a description test. Based on the results of hypothesis testing using T-test analysis, the value of Tcount is 4.309. The value of Tcount is 4.309 mote than Ttable 1.999 at a significance level of 0.05 then Ho is rejected, meaning that there is an influence of the Lectora Inspire-assisted POE learning model on students thinking skills on the bodys defense system material.